Thermal design framework of heat pipe heat exchanger for efficient waste heat recovery - Lee, Seungjae; Kang, Sukkyung; Kim, Yunseo; Geum, Gyohoon; Kong, Daeyoung; Shin, Dong Hwan; Lee, Seong Hyuk; Lee, Jungho; Lee, Hyoungsoon (Energy, 2025)
Recovering waste heat efficiently is crucial to addressing global energy challenges and mitigating climate change, positioning heat pipe heat exchangers (HPHXs) as a promising solution. However, the computational modeling of HPHXs, particularly for finned configurations, remains challenging due to high computational costs. Consequently, existing research predominantly focuses on unfinned heat exchangers, while the performance of finned designs is typically estimated using empirical correlations or experimental data. Comprehensive analyses of finned HPHXs undergoing phase changes remain scarce. This study addresses these challenges by introducing a thermal design framework that approximates heat pipes as solid conductors with effective thermal conductivity and models finned sections as porous media. This innovative framework not only streamlines computational modeling but also enables accurate thermal performance predictions without reliance on experimental data. Using the proposed framework, HPHXs were modeled with 95 copper two-phase closed thermosyphons (TPCTs) and baffles, providing precise thermal performance analysis. To validate the framework, a full-scale HPHX test module was developed and experimentally tested. The model successfully predicted the performance of an HPHX recovering 30.2 kW of waste heat, achieving a thermal effectiveness of 0.78 and predictive accuracy within ±6.2 % of the measured energy recovery rate. This research establishes a reliable and scalable methodology for designing efficient HPHXs, representing a significant advancement in industrial waste heat recovery systems.
Keywords: Computational modelling; Design frameworks; Heat pipe heat exchangers; Local thermal non-equilibrium; Local thermal nonequilibrium model; Nonequilibrium model; Performance; Porous medium model; Thermal designs; Waste-heat recovery; Local thermal nonequilibrium model; Porous media model; Waste heat recovery